Trend analysis of timber trade in Malaysia focused on wood-based industry sector - Nur Syaza Ramiza Radzuan (2019)
This study was conducted to determine the trend of timber trade in Malaysia focused on wood-based industry sector. The trend of trading was divided into its major products, major timber product, selected regions and countries. The study covers the trend analysis of timber trade in Malaysia for a period of ten years from 2006 to 2015. Data on timber trade were collected from statistics published by the Forestry Department Peninsular Malaysia (FDPM) and Malaysia Timber Industry Board (MTIB). The trend of timber trade in Malaysia focused on wood-based industry sector was conducted. The results depicted that the export showed a decreasing trend with the rate of 0.95%, 1.22% and 0.49% for logs, sawn timber and plywood respectively. Result showed that sawn timber is the highest in export value of major timber product while Asia is the most export region meanwhile Japan is the major country of export of timber and timber products. The five major timber and timber products export destinations by Malaysia were Japan, United States of America, India, Australia, and Singapore. The entire five destinations showed decreasing trend except United States of America.